THE IMPACT OF PAPER-BASED FEEDBACK AND ELECTRONIC FEEDBACK ON STUDENTS' ABILITY IN WRITING A DESCRIPTIVE TEXT - Pravitasari, Dayu (2016)
This study aims to discover the impact of paper-based feedback and electronic feedback to students' ability in writing a descriptive text. The quasi-experimental research method was employed. The sample is 48 students of tenth grade at one of senior high school in Cimahi in the academic year 2015/2016. The students were divided into three groups. The data were collected through students' score in writing a descriptive text through paper-based feedback, electronic feedback, and no feedback as pre-test, post-test. The questionnaire was used to reveal the students' students' preference. The obtained data were analyzed based on ESL Composition Profile proposed by Jacob et al (1981). The statistical computation showed that compared to the control group, students in both paper-based and electronic feedback showed improvement in writing accuracy, which means both paper-based and electronic feedback are effective to improve students' writing ability. Furthermore, the mean comparison between paper-based and electronic feedback showed that paper-based feedback is more effective to improve students' writing ability;--- Penelitian ini bertujuan untuk mengetahui pengaruh dari paper-based feedback dan electronic feedback terhadap kemampuan siswa dalam menulis teks deskriptif. Penelitian kuasi eksperimen dipakai dalam penelitian ini. Penelitian ini melibatkan 48 siswa kelas X di salah satu SMA di Cimahi tahun ajaran 2015/2016. Siswa tersebut dibagi menjadi 3 kelompok. Data yang dikumpulkan berupa nilai untuk kemampuan menulis teks deskriptif sebelum dan sesudah menerima paper-based feedback, electronic feedback, dan tidak mendapat feedback sebagai pre-test dan post-test. Angket juga dibagikan untuk mengetahui pilihan siswa atas variasi feedback yang mereka terima. Data yang didapat dianalisa berdasarkan ESL Composition Profile yang dikemukakan oleh Jacob et al (1981). Perhitungan secara statistik menunjukkan bahwa dibandingkan dengan kelompok pembanding, siswa yang menerima perlakuan berupa paper-based feedback dan electronic feedback menunjukkan peningkatan dalam akurasi menulis, yang dapat diartikan bahwa baik paper-based feedback maupun electronic feedback efektif untuk meningkatkan kemampuan menulis siswa. Selain itu, perbandingan mean antara kelompok yang menerima perlakuan paper-based feedback dan electronic feedback menunjukkan bahwa paper-based feedback lebih efektif untuk meningkatkan kemampuan menulis siswa.